2001
DOI: 10.1037/0022-0663.93.3.604
|View full text |Cite
|
Sign up to set email alerts
|

Importance of assessing spatial ability in intellectually talented young adolescents: A 20-year longitudinal study.

Abstract: At age 13, 393 boys and 170 girls scoring at the top 0.5% in general intelligence completed the Scholastic Assessment Test Mathematics (SAT-M) and Verbal (SAT-V) subtests and the Differential Aptitude Test (DAT) Space Relations (SR) and Mechanical Reasoning (MR) subtests. Longitudinal data were collected through follow-up questionnaires completed at ages 18, 23, and 33. Multivariate statistical methods were employed using the SAT-M, SAT-V, and a DAT (SR + MR) composite to predict a series of developmentally se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
361
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 489 publications
(388 citation statements)
references
References 38 publications
21
361
0
6
Order By: Relevance
“…Future research should aim to find out more about the development of this spatial ability and the ontogenesis of individual differences. Recent research has shown that individual differences in spatial skills are predictive of later careers in STEM disciplines (Shea et al 2001;Wai et al 2009). Therefore, it is of important practical relevance to learn more about individual differences in mental rotation abilities, their origins, and means to foster this spatial skill at a young age.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should aim to find out more about the development of this spatial ability and the ontogenesis of individual differences. Recent research has shown that individual differences in spatial skills are predictive of later careers in STEM disciplines (Shea et al 2001;Wai et al 2009). Therefore, it is of important practical relevance to learn more about individual differences in mental rotation abilities, their origins, and means to foster this spatial skill at a young age.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially clear in groups of highly gifted students who possess all three key Stratum II abilities-verbal, mathematical, and spatial-in sufficient measure to qualify for any job requiring them. For instance, a study of extraordinarily gifted youngsters (all were above IQ 160) classified them according to whether their SAT scores in math and verbal at age 13 were about the same, tilted clearly toward math, or tilted toward verbal (Lubinski et al, 2001). About three-quarters of those with a math tilt later majored in math, medicine, or inorganic/organic science.…”
Section: Challenge and Promise 16mentioning
confidence: 99%
“…Many different tasks aim to measure visuospatial abilities, and performance on these tasks is often considered an important predictor of general intellectual abilities (Shea, Lubinski, & Benbow, 2001). "Visuospatial abilities" is a grouping of several different types of abilities.…”
Section: Introductionmentioning
confidence: 99%